Did Theresa May Kill the War Powers Convention? Comparing Parliamentary Debates on UK Intervention in Syria in 2013 and 2018. Issue 2 (4th February 2021) - Strong, James
ABSTRACT: This article asks whether Prime Minister Theresa May's decision to bypass the House of Commons and order military action in Syria in 2018 killed the UK's nascent War Powers Convention, established most visibly when MPs vetoed an essentially similar operation under Prime Minister David Cameron in 2013. It finds that the War Powers Convention survives, but in a weakened state, subject to new caveats that significantly narrow its scope. What happens next depends on the dynamic, unpredictable interaction between what future prime ministers believe, what strategic questions arise and what MPs will accept.